Effect of a low-cost virtual reality system on reducing pain and anxiety in adult burn injury patients during physiotherapy - Morris, Linzette Deidre (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Interdisciplinary Health Sciences. Physiotherapy))--University of Stellenbosch, 2009.